Recollecting Landscapes. Rephotography, Memory and Transformation 1904-1980-2004-2014. - Notteboom, Bruno; Uyttenhove, Pieter; Debergh, Reinout; Vanbelleghem, Dries; Van Bouwel, Ive; Vanhecke, Leo; Willequet, Benoît (Amsterdam : Roma Publications, 2018)
Charlier, Georges ; De Cleene, Michiel ; Kempenaers, Jan ; Massaert, Jean
boek